Clinical efficacy of laparoscopic closed hernia ring combined with a patch repair for Gilbert type III indirect inguinal hernia - Binyu, Luo; Qin, Zhang; Xiao, Zhang; Daquan, Zhang; Qing, Guo; Jing, Yu; Yunhong, Tian; Mingyang, Ren (Frontiers in Surgery, 2023)
Purpose The incidence of seroma and postoperative pain after Gilbert type III inguinal hernia repair is high. To reduce postoperative complications, this study investigated the clinical efficacy of laparoscopic closed hernia ring combined with a patch repair for Gilbert type III indirect inguinal hernia. Methods Through a prospective randomized controlled study, a total of 193 patients with Gilbert type III indirect inguinal hernia admitted to Nanchong Central Hospital affiliated with Chuanbei Medical College from May 2020 to December 2021 were selected and randomly divided into the inner ring closed group (85 patients) and the inner ring non-closed group (95 patients). The patients in both groups underwent laparoscopic tension-free repair of their inguinal hernias. General information such as operative time, postoperative hospital stay, and hospital cost were compared between the two groups, and the patients were followed up at 1, 7, 14, 21, and 28 days and then 3, 6, and 12 months after surgery to compare complications such as incidence of seroma, volume of the seroma fluid, incidence of pain, and visual analogue scale (VAS) pain score. Results There was no conversion to open procedures in any of the patients. The operation time of the closed group was significantly longer than that of the non-closed group (64.2 ± 12.2 vs. 55.3 ± 9.5 min, P < 0.01). The proportion of patients with postoperative pain in the two groups was 39 (46%) vs. 59 (62%), P = 0.029 on 7 days; 17 (20%) vs. 33 (35%), P = 0.028 on 14 days; and 6 (7%) vs. 22 (23%), P = 0.003 on 21 days in the postoperative closed group and was significantly lower than that in the non-closed group, while we found that the non-closed group had a higher VAS pain score than that of the closed group (2.36 ± 0.61 vs. 1.95 ± 0.71, P = 0.003 on 7 days and 2.12 ± 0.49 vs. 1.65 ± 0.49, P = 0.002 on 14 days) after surgery according to the statistical results of the VAS pain score. The incidence of postoperative seroma and the amount of seroma fluid decreased gradually in both groups, but when comparing the two groups, the proportion of cases of seroma in the closed group on 7 days [45 (53%) vs. 79 (83%), P < 0.01]; 14 days [23 (27%) vs. 43 (45%), P = 0.011]; and 21 days [10 (12%) vs. 29 (31%), P = 0.002] after the operation were significantly less than that in the non-closed group. For the comparison of the amount of seroma fluid between the groups, the seroma fluid volume in the non-closed group was greater than that in the closed group (34.48 ± 20.40 vs. 43.87 ± 16.40 ml, P = 0.006, 7 days) and (21.79 ± 8.42 vs. 30.74 ± 10.39 ml, P = 0.002, 14 days) after surgery. There were no differences in the length of stay, total hospital costs, or postoperative complications (urinary retention, intestinal obstruction, nausea, vomiting, bleeding, and infection) between the two groups, and the differences were not statistically significant (P > 0.05). The postoperative follow-up period was 3–20 months, and no chronic pain or recurrence occurred during the postoperative follow-up period in either group. Conclusions Closure of the hernia ring is safe and effective for laparoscopic hernia repair for Gilbert type III inguinal hernia, and it significantly reduces the incidence of postoperative seroma and further reduces the postoperative pain without increasing the risk of postoperative infection and recurrence.